Proteome-wide identification of poly(ADP-Ribosyl)ation targets in different genotoxic stress responses - Jungmichel, Stephanie; Rosenthal, Florian; Altmeyer, Matthias; Lukas, Jiri; Hottiger, Michael O; Nielsen, Michael L (Molecular cell, 2013)
Poly(ADP-ribos)ylation (PARylation) is a reversible posttranslational modification found in higher eukaryotes. However, little is known about PARylation acceptor proteins. Here, we describe a sensitive proteomics approach based on high-accuracy quantitative mass spectrometry for the identification of PARylated proteins induced under different cellular stress conditions. While confirming the majority of known PARylated substrates, our screen identifies numerous additional PARylation targets. In vivo and in vitro validation of acceptor proteins confirms that our methodology targets covalent PARylation. Nuclear proteins encompassing nucleic acid binding properties are prominently PARylated upon genotoxic stress, consistent with the nuclear localization of ARTD1/PARP1 and ARTD2/PARP2. Distinct differences in proteins becoming PARylated upon various genotoxic insults are observed, exemplified by the PARylation of RNA-processing factors THRAP3 and TAF15 under oxidative stress. High-content imaging reveals that PARylation affects the nuclear relocalization of THRAP3 and TAF15, demonstrating the potential of our approach to uncover hitherto unappreciated processes being controlled by specific genotoxic-stress-induced PARylation.